ПУТИ АКТИВНОГО ВНЕДРЕНИЯ ИННОВАЦИИ С ЦЕЛЬЮ ПОВЫШЕНИЯ КАЧЕСТВА ОБУЧЕНИЯ - Юсупова, Ф.З. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of improving the educational process by using innovative methods of teaching. The author of the article suggests using the new forms of lecture- a lecture-visualization, a problem lecture, a lecture-press couference in combination with modern technical means, creating schemes, slides, graphics and other visual materials.
Keywords: educational process; methods of teaching; traditional methods; innovative approach; teaching aids; quality of knowledge